The trajectory simulation of an anti-submarine missile motion - Nguyen Hanh, Dr Hoan; Nguyen Van Hoa; Dang Van Hung; Le Tuan Anh (Journal of Military Science and Technology, 2025)
This paper analyses an anti-submarine missile's aerial motion, water entry motion and under- water motion. It establishes equations of motion for each phase and presents the ballistic characteristics of each section. According to the model, a trajectory is simulated. The method and the result provide an efficacious guarantee for the operational employment of an anti-submarine missile. It thus provides a basis for the design and calculation of an anti-submarine missile.